Barriers and enablers to opioid deprescription: A qualitative study. - Rebecca Lawrence; Everett Versteeg; Andrea Pike; Holly Etchegary; Amanda Hall (PLoS ONE)
Background Canada has the fourth highest per capita rate of opioid prescriptions in the world, contributing to the country's opioid crisis. Due to both their pain-relieving and euphoric properties, opioids can be highly addictive, leading to potential overdose and death. Deprescription is an endorsed and organized method of discontinuing a drug but very little is known about the barriers that Canadian physicians face when attempting to deprescribe opioids, particularly those who practice in rural areas (which have some of the highest rates of opioid users). Methods This was an explorative, qualitative study describing rural family doctors' experiences and practices regarding opioid deprescription in primary care. A convenience sample of family doctors who had experience working with patients taking opioid medications was recruited from the professional networks of study team members. After consenting to participate, data was collected using semi-structured telephone interviews and analyzed by researchers experienced in applying the Theoretical Domains Framework to assess barriers and enablers of behavior change. Principal findings 10 physicians participated in this study. Our analysis revealed four barriers and five enablers related to opioid deprescription in rural primary care. Barriers include a lack of knowledge and skills related to deprescribing, discomfort initiating deprescription, patient pressure to continue prescribing opioids, and a lack of foundational support required to deprescribe. Enablers include working with colleagues who share common views on overuse of opioids and deprescription; access to other healthcare providers, community-based resources, and clinical tools; using a systematic approach to deprescription; previous experience successfully deprescribing opioids; and practicing in a rural setting. Conclusions Opioid dependence and over-prescription continue to be a problem for our health system. Deprescription is necessary but challenging for family physicians. Rural physicians are keenly aware of the importance of preserving the physician-patient therapeutic relationship and open and clear communication about opioid medications and deprescription but feel unprepared to manage this in the face of difficult issues surrounding deprescription. They also feel unprepared to deal with deprescription effectively without access to other resources, healthcare professionals, patient education materials and time. Rural physicians would benefit most from added foundational supports for deprescription.